Tietoturvatietoisuus eduskunnassa - Järvinen, Sami (2025)
As digitalization has become more widespread, information systems have proliferated and the attacks against them have evolved into ever more com-plex forms. Human error remains one of the leading causes of security inci-dents, and in response organizations have begun to offer cybersecurity train-ing to their staff to reduce vulnerabilities. Effective training has been shown to have a significant impact on the prevailing security behavior within an organ-ization. An individual’s cybersecurity awareness serves as a useful measura-ble construct because it encompasses one’s attitudes, behaviors, and knowledge of security issues in accordance with the KAB model. By measur-ing security awareness, an organization can assess its personnel’s readiness to confront security challenges as well as their attitudes toward existing policies. Awareness metrics also reveal specific areas that may require additional train-ing or resources. In this study, we measured the cybersecurity awareness of Finland’s parliament and associated agencies using a quantitative online ques-tionnaire. The purpose was to assess the current state of staff information se-curity awareness and to identify topic areas that require more attention in training. Awareness was measured based on the KAB model by assessing re-spondents’ information security knowledge, information security behavior and information security attitude. The survey responses were given using a 5-point Likert scale. The results indicate that respondents display strong overall security awareness, with no critical deficiencies identified. However, the data also highlights a few weaker areas that can now be targeted for improvement in the future training and resource allocation.